Hell – Is Other People! A Genetic Theory of Personal Relations (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
By adopting a genetic methodology, a theory of personal relations has been developed that both accounts for the worst and allows for the best in human relationships. Sartre's method of a 'dialectical degeneration' is employed to account for our Alienation from each other while Empathy and Sympathy are introduced to allow for the closeness of a personal rapport.
Keywords: 'Genetic'; 'Phenomenology'; 'Ontology'; 'Empathy'; 'Alienation'; 'Isolation'; 'Sympathy'; 'Love'; 'Friendship'; 'Co-operation'